Perioperative pulmonary aspiration: An analysis of 28 reports from the thai anesthesia incident monitoring study (Thai AIMS) - Klanarong S. (2017)
Objective: To study the patients' characteristics, outcomes, contributory factors, factors minimizing the incidence and suggested corrective strategies for perioperative pulmonary aspiration in Thailand. Materiel and Method: This is a prospective descriptive research design. The relevant data was extracted from the incident reports on aspiration from 51 hospitals across Thailand during the study period between January 1 and June 30, 2007 from the Thai Anesthesia Incident Monitoring Study (Thai AIMS) database. Descriptive statistics was used. Each incident report was reviewed by three senior anesthesiologists. Any disagreement was discussed to achieve a consensus. Results: From 1,996 incident reports, there were 28 reports (1.4%) that met the definition of pulmonary aspiration. Most of the incidents occurred in patients with ASA 1-2 (85.7%), during the official hour (64.3%) and the anesthesiologists were in charge (67.9%). Eleven incidents (39.3%) occurred during induction, seven (25%) during maintenance and seven (25%) during emergence phases. Anesthetic factors played an important role in 26 incidents (92.9%). All the incidents except one (96.4%) were considered human errors and 25 (89.2%) were preventable. Of the incidents caused by human errors, nine (32.1%) were caused by skill-based errors. Thirteen patients (46.4%) had major physiologic changes and 10 (35.7%) of them needed unplanned ICU admission. Ten patients (35.7%) needed prolonged ventilator support and two (7.14%) of them died. Conclusion: The contributing factors that might lead to the incidents were improper decision (75%), lack of experience (53.5%) and lack of knowledge (21.4%). Factors minimizing incident, were vigilance (85.7%), having experienced assistant (50%) and experience in that situation (25%). Suggested preventive strategies were guidelines practice in anesthetic management (67.8%), improvement of supervision (57.1%), additional training (42.8%) and quality assurance activity (28.6%).